Efektivitas Metode Demontrasi Dalam Meningkatkan Pemahaman Tata Cara Shalat Santri - Syam, Khairil; Hermansyah, Ainani; Ayyun, Qurrata; Khatimah, Nurul; Rahmadani, Rani; Danial, Danial; Syarifuddin, Syarifuddin (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2024)
This study aims to improve students' understanding of the procedures for performing prayers through the application of the demonstration method in class BP 1 at RQS Qudwatun Hasanah. This research is a Classroom Action Research (CAR) using a qualitative descriptive method. Data collection techniques include observation, tests, and documentation. The study was conducted in one cycle consisting of four stages: planning, action implementation, observation, and reflection. The results of the study showed a significant improvement in students' understanding after the implementation of the demonstration method. Students' understanding scores in the pre-cycle were 55.34%, categorized as poor, which increased to 88.86% in cycle I, categorized as very good. The N-gain calculation reached 0.75, indicating a high improvement level. Based on these findings, it can be concluded that the demonstration method is effective in improving students' understanding of the procedures for performing prayers in the Islamic Education subject at RQS Qudwatun Hasanah.